PELATIHAN BAHASA INGGRIS UNTUK MAHASISWA KAWASAN TIMUR INDONESIA: SEBUAH KEBUTUHAN DI ERA GLOBAL - Listyani, Listyani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service (PkM) is one of the tridharma pillars of higher education. Lecturers are required to carry out the tri dharma of higher education, which consists of education or teaching, research, and community service. This article carries the theme of a community service program, which is about English language training for students from eastern Indonesia who are studying at a private university in the city of Salatiga, Central Java. More precisely, these students came from NTT, Lombok, and Papua. This program takes place from October to December 2022. The training was held offline and was attended by five (5) students. They lived in a dorm and were under the care of a foundation named Yayasan Komunitas Cahaya Indonesia. In general, all the activities ran well and smoothly.